Rancang Bangun Aplikasi Duplicate Docx Scanner Menerapkan Metode SHA-256 - Adelina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Hard drives are one of the core components of a computer in various types and sizes. Large hard disks can become full, even though they don't feel like storing large files. The possibility of saving the same file in the directory is very difficult and will take a long time. The Duplicate Docx Scanner application is able to solve this problem. The Duplicate Docx Scanner application is able to find out the same file is located in a different directory by determining the directory on the hard disk and other storage media. This application can calculate the hash value so that it can find the same file. The Duplicate Docx Scanner application uses the SHA-256 hash method. SHA-256 is used to perform file integrity checks in a variety of situations. This Duplicate Docx Scanner application is designed to use the Microsoft Visual Basic.Net 2008 programming language